Pengaruh Lingkungan Kerja non Fisik, Rotasi Kerja, Karakteristik Demografi terhadap Pengembangan Karir dan Prestasi Kerja Karyawan BPJS Ketenagakerjaan se-Provinsi Nusa Tenggara Barat - Mardian Rizka Harsani; Agusdin Agusdin; Mukmin Suryatni (Jurnal Pendidik Indonesia (JPIn), 2022)
Career development and employee performance are not just a coincidence, but many factors influence it, namely the work environment, job rotation and demographic characteristics. The purpose of this study was to determine the effect of non-physical work environment, job rotation, demographic characteristics on career development and work performance of BPJS Ketenagakerjaan employees throughout the province of West Nusa Tenggara. This research uses associative research method. The sample in this study amounted to 42 people. The instrument used in this research is a questionnaire. The data were analyzed using multiple regression with the help of the SPSS program. Based on the results of the study, it can be concluded that the non-physical work environment, job rotation, and demographic characteristics have a significant effect on career development and work performance of BPJS Ketenagakerjaan employees throughout the province of West Nusa Tenggara.